Dampak Konsolidasi Keuangan Terhadap Likuiditas, Profitabilitas, dan Ekuitas-Earning Based: Studi Kasus Pada PT Indofood Sukses Makmur Tbk (INDF) - Ghina Wahdiyanti; Maya Lizqiyanti; Taupan Irmansyah; M. Masrukhan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Financial consolidation has become a crucial strategy for multinational companies in addressing increasingly intense global competition. It is often employed as a primary approach to expand market reach and drive corporate growth, ultimately affecting liquidity, equity-earning based measures, and profitability. This study specifically examines the impact of consolidation on a company's liquidity, equity-earning based metrics, and profitability using financial ratio analysis, including Current Ratio (CR), Earnings Per Share (EPS), and Net Profit Margin (NPM) as key indicators. Adopting a quantitative approach, the research utilizes secondary data from the financial statements of PT Indofood Sukses Makmur Tbk before and after consolidation in 2023. The methods applied include a comparison of financial statement items pre- and post-consolidation and a literature review relevant to financial performance analysis. The data analysis results reveal that post-consolidation, PT Indofood Sukses Makmur Tbk recorded an increase in liquidity ratio (current ratio) by 15.26%, reaching 1.9171, and an equity-earning based ratio (earnings per share) rise of 53.74% to 0.001309, which positively impacted the company. However, profitability ratio (net profit margin) declined by 22.81% to 0.1028, indicating challenges in cost management and operational efficiency following the consolidation.